THE EMPEROR TRAJAN AND THE PETITION OF THE BITHYNIAN ATHLETES, (PLIN., EP. 118-119): ‘LEX RETRO NON AGIT’…? - Jońca, Maciej (Zeszyty Prawnicze, 2018)
The material used by Professor Witold Wołodkiewicz in his analysis of the lex retro non agit principle may be supplemented with one more source – one which has been underestimated and referred to only incidentally, but may eﬀectively tip the balance of the discussion. Book Ten of Pliny’s correspondence consists of letters addressed to Trajan, including some replies from the Emperor. It contains material which gives the perfect answer to the search for the origins of the lex retro non agit principle. In a list of unresolved issues Pliny mentions a specific request made by professional athletes, who wanted him to apply some regulations which the Emperor had just instituted, as grounds in their favour. But both the Emperor and Pliny, his governor for Bithynia, concur that in this case it would be inadmissible to make the new provisions retroactive.